Internet Debates: Generations X, Y and Z - G. B. Elagin; I. B. Mikirtumov (Дискурс)
Introduction. The theory of generations by Neil Howe and William Strauss has become an integral part of “folk sociology” today, so that everyone somehow asks the question of which generational group he / she belongs to and what behavior is expected of him / her, in particular, in network communications. The behavior of representatives of different generational groups in network disputes based on self-identification remains no sufficiently investigated. In this article we present the results of an argumentative and pragmatic analysis of the specifics of the argumentation of representatives of generations X (born in the p eriod f rom 1 967 to 1981), Y ( born f rom 1 982 t o 2 003) and Z ( born a fter 2004), who fell into an uncomfortable situation of a network dispute.Methodology and sources. The research is of a qualitative nature and its task is to formulate well-grounded assumptions about the connections of generational groups with certain argumentative means, among which are rhetorical techniques, sociolect, speech actions. The material of the study was comments on entries in thematic groups, discussions in chats and on the ”walls” of social networks (”VKontakte”, ”Facebook”, ”Instagram”), as well as some other sources (”Avito”, ”Twitter”, ”Snob.ru”). The selection of material is focused on finding the typical. The research focuses on uncomfortable for the participants moments of disputes, understood as situations that are most prompting for an identifying self-presentation.Results and discussion. The materials studied make it possible to formulate the following assumptions. First, representatives of generations X, Y and Z use different techniques in difficult situations of network disputes. X apply the classic ”argument to age”. Y use the sociolect of trust and immediacy to shift the focus of the dispute, while in other cases they resort to a sociolect that contains a morally binding component. For Y a network dispute engenders a minimum of commitment and easily turns into a rhetorical skill competition. Z view network disputes as a platform for resolving negative affects. In an uncomfortable situation they use the techniques of verbal aggression, shifting the focus of the dispute to the justification of this very action. All three groups act in anticipation of the support of a sympathetic audience. The described types of behavior identify the representative of the generational group as for other participants in communication.Conclusion. The features of generational groups, which are indicated by sociological data, convincingly explain the strategy of behavior of their representatives in difficult situations of network disputes. But it should be borne in mind that such strategies themselves and the argumentative and linguistic means suggested by them become patterns of generational identity. The socio-cultural dynamics of generations is therefore also associated with how these patterns will change in connection with changes in the network communication environment.